â€œPengaruh Brand Community Terhadap Loyalitas Merek Sepeda Motor Yamaha Vixionâ€ (Deskripsi penelitian di Kec. Ambulu Kab. Jember) - Pambudi, Rifki Agung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Tougher competition for market indirectly force motorcycle manufacturers to maintain customer loyalty. With the rise of emerging community that no other marks is the community taking a brand and model of vehicle, car manufacturers believe that community is a potential market of the future. The problem we face is the consumer brand loyalty will be very necessary for a company to maintain its market share. Brand Community how can automakers maintain fidelity to the members of the brand community. This research analyzes the influence of brand communities to brand loyalty. This study uses multiple regression analysis with SPSS version 11.5. This data collection method uses a questionnaire to members of the community of Yamaha Vixion in Ambulu. Questionnaire method used to determine further what factors were behind the brand loyalty of Yamaha Vixion so community members decided to remain faithful to use the Yamaha Vixion. Questionnaires were distributed 40 questionnaires. The results showed six variables: the legitimacy of the brand community, oppositional brand loyalty, celebrating the history of the brand, sharing brand stories, integrating and retain members, and assisting in the use of the brand, which is significant oppositional brand loyalty, sharing brand stories, integrating and retain members, and assisting in the use of the brand. Â Keywords: brand loyalty, brand community